PENGARUH BERPIKIR KRITIS TERHADAP HASIL BELAJAR MATEMATIKA SMAN 3 PAREPARE - Dilla Pratiwi (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2024)
Some students have difficulty working on mathematics problems systematically. This shows that the level of critical thinking of students is still very lacking. The level of critical thinking can influence mathematics learning outcomes. The research carried out was an Ex Post Facto type of research using a quantitative approach to determine the influence of the level of critical thinking on mathematics learning outcomes for students in class X MIPA 3 UPT SMA Negeri 3 Parepare. The results of descriptive statistical analysis obtained data which showed that the Critical Thinking Level of class The students' learning outcomes are in the